(3GdehShYI GdadcjI GdcHQi hCSQGQgG (B=s Astronomical encyclopedia : (3JGQjNgG (B- (3CbSGegG (B- (3CMcGegG (B- (3EYLGRgG (B- (3YdeGFgGs - (3YhGLg, eMeO UGHQs; (3UdGM, eQhIs ((3GdefhajI, eUQs (3MhGOjJ ddfTQ hGdJhRjYs, 2024)
(3cJGH GdehShYI GdadcjI JGQjNgG (B- (3CbSGegG (B- (3CMcGegG (B- (3EYLGRgG (B- (3YdeGFgG (B. (3ddeDda GdOcJhQ eMeO UGHQ YhGLg(B. (3Efg Yde Gdadc GdPj dGjYdg hdG jbJQH efg Yde BNQ GdYde GdPj EPG GNJai (B((3aQVjG(B) (3SJNJaj eYg MVGQGJ GdYUQ GdMGdj, hJRhd MbGFb GdeGVj, ajehJ GdeSJbHd JdbGFjGs
Keywords: (3Gdadcs; (3GdchGcHs; (3GdeLQGJs